The Abused Aspect: Neglecting the Influence of a Verb's Lexical Meaning on Tense-Form Choice - Merkle, Benjamin L. (Bulletin for biblical research, 2016)
The recent prominence of verbal aspect theory has played an important role in helping NT exegetes more accurately interpret the use and meaning of verbs. In seeking to correct the abuses of the past, however, modern interpreters who embrace verbal aspect theory are also often guilty of placing too much interpretive weight on the tense-form of verbs, often describing them as being "marked." Focusing on imperatives, this essay demonstrates that verbs that are often highlighted as being emphasized by some scholars are simply the normal, expected form of that verb. In other words, sometimes an author does not make a subjective choice to portray an action in a certain way but submits to convention and uses the normal or expected form which is often influenced by a particular verb's inherent lexical meaning.